PENGARUH EFEKTIVITAS KOMITE AUDIT, KONDISI KEUANGAN, KOMPLEKSITAS OPERASI, PROFITABILITAS, DAN KARAKTERISTIK AUDITOR EKSTERNAL TERHADAP AUDIT REPORT LAG (Stude Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia pada Tahun 2017-2019) - Shabilla Ariningtyastuti; Abdul Rohman (Diponegoro Journal of Accounting, 2021)
The purpose of this research is to examine the effect of effectiveness of the audit committee, financial condition, operational complexity, profitability, and external auditor characteristics to audit report lag on manufacturing companies. Variables used in the examination are effectiveness of the audit committee, financial condition, operational complexity, profitability, auditor reputation, tenure audit, and specialization industrial auditor as the independent variables, also audit report lag as the dependent variable.This research used manufacturing companies during the 2017-2019 with total sample is 351 samples. Sampling based on purposive sampling method that follows certain criteria(s). Multiple regression analysis is the analysis method used in this research. The results of this study indicates that effectiveness of the audit committee and profitability have a negative significant effect on audit report lag. Audit tenure has a positive significant on audit report lag. Beside that, auditor reputation and specialization industrial auditor have a negative and insignificant on audit report lag. Financial condition and operational complexity have a positive and insignificant on audit report lag. Audit tenure has a positive significant on audit report lag.